Porous TaC ultrahigh-temperature ceramic and preparation method thereof
By using metal element, carbon powder and metal oxide as pore-forming agents, combined with the control of sintering conditions, porous TaC ultra-high temperature ceramics with high porosity and strength were prepared, which solved the problem of insufficient research on ceramic pore structure in the prior art. , meets the needs of high-temperature applications in the fields of aerospace and other fields.
Patent Information
- Application Number
- CN202411779465.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-14
AI Technical Summary
The pore structure of porous ultra-high temperature ceramics has not been specifically studied in the prior art, resulting in insufficient mechanical properties and high temperature stability, which makes it difficult to meet the application needs in the fields of aerospace and other fields.
By using a specific first pore-forming agent and a second pore-forming agent, including metal element, carbon powder and metal oxides that can react with TaC, the sintering conditions and the type and ratio of the pore-forming agent are prepared. Porous TaC ceramics.
The porosity of porous TaC ultra-high temperature ceramics is 5%-40%, and the compression and fracture strength is ≥500Mpa, which improves the mechanical properties and high temperature stability of the ceramics. It is suitable for thermal protection systems in aerospace and other fields.
Smart Images

Figure BDA0005173896260000091 
Figure HDA0005173896430000011 
Figure HDA0005173896430000012
Abstract
Description
Technical Field
[0001] The present invention relates to the field of porous ceramic materials, and more specifically, to a porous TaC ultrahigh temperature ceramic and a preparation method thereof. Background Art
[0002] The melting point of ultra-high temperature ceramic materials is usually above 3000℃, or at least can be used in high temperature, corrosion-containing, oxygen-resistant environment above 2000℃. The materials cover transition metal borides, carbides, nitrides and their composite ceramics. It is a non-ablative ultra-high temperature heat-resistant material with great development potential and has become an important candidate material system for thermal protection systems in aerospace applications. Dry forming, colloidal forming, and liquid precursor forming are currently the common methods for preparing porous ultra-high temperature ceramics. Research on porous ultra-high temperature ceramics with higher mechanical properties, high temperature stability, and controllable pore structure has broad prospects for expanding the practical application of ultra-high temperature ceramics. However, no specific research on porous structures has been conducted in the prior art. Summary of the invention
[0003] A porous TaC ultrahigh temperature ceramic is sintered by preparing raw materials, wherein the preparing raw materials include a pore former and TaC powder, and the pore former includes a first pore former and a second pore former; the first pore former includes a metal element and carbon powder, and the second pore former includes a metal oxide that can react with TaC, wherein the porous TaC ultrahigh temperature ceramic has a porosity of 5%-40%, a compression fracture strength of ≥500Mpa, a melting point of the metal element is T1, a melting point of the second pore former is T2, and 1495°C≤T1≤T2.
[0004] The present application has found that the metal element of the first pore-forming agent, carbon powder and the metal oxide of the second pore-forming agent can be used in combination to prepare porous TaC ceramics with dense pores. During the preparation of the raw materials and the stacking of the pore-forming agent, gaps exist due to the steric hindrance between the particles. Specifically, when preparing porous TaC ultra-high temperature ceramics, the metal oxide acts as the second pore-forming agent to react with TaC powder to generate gas to form a porous structure. The melting point of the metal element is between 1495°C and the melting point of the second pore-forming agent. The metal element flows in a liquid state and will act as a sintering agent to promote the shrinkage and recrystallization of the TaC powder, thereby generating certain pores. The carbon powder will volatilize and sublimate at high temperatures and promote the generation of pores. Pores will be formed after sintering and volatilization.
[0005] By controlling the sintering conditions and the type and ratio of the pore-forming agent, the present application can achieve the desired pore distribution of the ceramic material while maintaining a certain density, and achieve a porosity of 5%-40% and a compressive fracture strength of ≥500Mpa for the porous TaC ultrahigh temperature ceramic.
[0006] Furthermore, the average particle size of the metal element is 0.1 μm-5 μm.
[0007] Preferably, the average particle size of the metal element is comprised between 0.1 μm and 3 μm.
[0008] More preferably, the average particle size of the metal element is comprised between 0.5 μm and 3 μm.
[0009] As an example, the average particle size of the metal element may be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.
[0010] The average particle size of the carbon powder is comprised between 10 nm and 100 nm.
[0011] Preferably, the average particle size of the carbon powder is 10nm-80nm.
[0012] More preferably, the average particle size of the carbon powder is 20 nm-80 nm.
[0013] As an example, the average particle size of the carbon powder may be 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 75 nm or 80 nm.
[0014] The average particle size of the metal oxide is comprised between 0.1 μm and 3 μm.
[0015] Preferably, the average particle size of the metal oxide is comprised between 0.1 μm and 2 μm.
[0016] More preferably, the average particle size of the metal oxide is comprised between 0.5 μm and 2 μm.
[0017] As an example, the average particle size of the metal oxide may be 0.5 μm, 1 μm, 1.5 μm or 2 μm.
[0018] The weight ratio of the pore former to TaC powder is 1:(1-10), which can effectively increase the density of the ceramic and generate pores. It may be that after the sintering reaction, the smaller gap between the TaC powder and the pore former will be eliminated through volume shrinkage and grain diffusion, while the larger gap between the TaC powder and the pore former will form pores. When the pore former content is lower than 1:10 or higher than 1:1, the effect of high densification and pores cannot be achieved.
[0019] Preferably, the weight ratio of the pore former to TaC powder is 1:(2-8).
[0020] Further preferably, the weight ratio of the pore former to TaC powder is 1:(2-7).
[0021] The weight ratio of the metal element, carbon powder and metal oxide is 1:(0.2-5):(0.2-5).
[0022] Preferably, the weight ratio of the metal element, carbon powder and metal oxide is 1:(0.2-2):(0.2-2).
[0023] Further preferably, the weight ratio of the metal element, carbon powder and metal oxide is 1:(0.5-1.5):(0.5-1.5).
[0024] Preferably, the melting point of the metal element is greater than 1495°C.
[0025] Further preferably, the melting point of the metal element is 1495°C-3000°C.
[0026] As an example, the melting point of the metal element may be 1495°C, 1600°C, 1800°C, 2000°C, 2200°C, 2400°C, 2600°C, 2800°C or 3000°C.
[0027] The metal element includes at least one of titanium, iron, cobalt, nickel, molybdenum, chromium and zirconium.
[0028] Preferably, the metal element includes at least one of titanium, iron, cobalt, nickel, chromium and zirconium.
[0029] Further preferably, the metal element includes at least one of titanium, iron, cobalt and nickel.
[0030] The metal oxide includes at least one of iron oxide, aluminum oxide, copper oxide, titanium dioxide and iridium dioxide.
[0031] Preferably, the metal oxide includes at least one of iron oxide, aluminum oxide and copper oxide.
[0032] Further preferably, the metal oxide comprises iron oxide and / or aluminum oxide.
[0033] The applicant has found that the pore-forming agent includes a metal element, carbon powder and a metal oxide, and the weight ratio of the metal element, carbon powder and metal oxide is 1:(0.2-5):(0.2-5), which can prepare a dense, high-porosity TaC porous ceramic based on excellent crystallinity.
[0034] A second aspect of the present invention provides a method for preparing a porous TaC ultrahigh temperature ceramic, comprising the following steps:
[0035] S1, mixing the TaC powder and the pore-forming agent uniformly to form a mixture;
[0036] S2, cold pressing the mixture to form an embryo body;
[0037] S3, sintering the embryonic body in an inert gas atmosphere.
[0038] The mixing in step S1 includes mixing using ball milling media.
[0039] The ball milling process includes: ball milling at a rotation speed of 200-1000 r / min for 6-48 hours.
[0040] Preferably, the ball milling process includes: ball milling at a rotation speed of 200-800 r / min for 6-36 h.
[0041] The ball milling process further includes: ball milling at a rotation speed of 300-800 r / min for 12-36 hours.
[0042] Preferably, the shape of the mixture includes spherical and irregular shapes.
[0043] The average particle size of the powder of the mixture is 1 μm-5 μm.
[0044] Preferably, the average particle size of the powder of the mixture is 1 μm-4 μm.
[0045] More preferably, the average particle size of the powder of the mixture is 2 μm-4 μm.
[0046] As an example, the average particle size of the powder of the mixture may be 2 μm, 2.5 μm, 3 μm, 3.5 μm or 4 μm.
[0047] The cold pressing step includes: filling the mixture into a mold evenly, and applying pressure to the filled powder using a hydraulic press to form an embryonic body.
[0048] The embryo body has a diameter of 6 mm to 12 mm and a thickness of 0.1 mm to 5 mm.
[0049] Preferably, the embryo body has a diameter of 8 mm to 12 mm and a thickness of 0.1 mm to 4 mm.
[0050] More preferably, the embryo body has a diameter of 9 mm to 11 mm and a thickness of 2 mm to 4 mm.
[0051] As an example, the diameter of the embryo body may be 9 mm, 9.5 mm, 10 mm, 10.5 mm or 11 mm.
[0052] As an example, the thickness of the embryonic body may be 2 mm, 2.5 mm, 3 mm, 3.5 mm or 4 mm.
[0053] The cold pressing pressure is 1MPa-35MPa, and the pressure holding time is 0.5min-5min.
[0054] Preferably, the cold pressing pressure is 1 MPa-20 MPa, and the holding time is 0.5 min-3 min.
[0055] Further preferably, the cold pressing pressure is 1 MPa-10 MPa, and the holding time is 1 min-3 min.
[0056] The sintering process steps include: first heating to 1300-1500°C at 3°C / min-5°C / min, then heating to 1500-2000°C at 1°C / min-3°C / min, then heating to 2000-2600°C at 0.3°C / min-2°C / min, and keeping warm for 0.1h-3h.
[0057] The present invention limits specific gradual temperature increase steps, which can prevent the embryo body from being deformed, broken, and peeled during the high-temperature sintering process, and further improve the stability of the ceramic.
[0058] Preferably, the sintering process steps include: first heating to 1300°C-1500°C at 3°C / min-4°C / min, then heating to 1500°C-2000°C at 1.5°C / min-3°C / min, then heating to 2500°C-2600°C at 0.5°C / min-1.5°C / min, and continuing to keep warm for 0.1h-0.5h.
[0059] By limiting the sintering process to heat up to 2500℃-2600℃ and keeping it warm for 0.1h-0.5h, the amount of pore-forming agent added can be reduced while further improving the crystallization performance and pore uniformity of the ceramic. It can be used in the form of graphite coated parts to meet the application of thermal field materials in the field of semiconductor equipment, play a role in gas phase filtration and diversion, and have an excellent service life.
[0060] Further preferably, the sintering process steps include: first heating to 1300°C-1500°C at 3°C / min-3.5°C / min, then heating to 1500°C-2000°C at 1.5°C / min-2.5°C / min, then heating to 2000°C-2600°C at 0.7°C / min-1.2°C / min, and continuing to keep warm for 0.1h-0.5h.
[0061] The sintering process also includes: after the insulation is completed, first cooling to 1500°C-2000°C at 0.3°C / min-2°C / min, then cooling to 1300°C-1500°C at 1°C / min-3°C / min, and then cooling to 20-40°C at 3°C / min-5°C / min.
[0062] Preferably, the sintering process step also includes: after the insulation is completed, first cooling to 1500℃-2000℃ at 0.5℃ / min-1.5℃ / min, then cooling to 1300℃-1500℃ at 1.5℃ / min-3℃ / min, and then cooling to 20-40℃ at 3℃ / min-4℃ / min.
[0063] Further preferably, the sintering process step also includes: after the insulation is completed, first cooling to 1500℃-2000℃ at 0.7℃ / min-1.2℃ / min, then cooling to 1300℃-1500℃ at 1.5℃ / min-2.5℃ / min, and then cooling to 20-40℃ at 3℃ / min-3.5℃ / min.
[0064] Beneficial Effects
[0065] 1. The present invention adopts a specific first pore-forming agent and a second pore-forming agent, wherein when the first pore-forming agent includes a metal element and carbon powder, and the second pore-forming agent includes a metal oxide that can react with TaC, and the melting point of the metal element is between 1495°C and the melting point of the second pore-forming agent, the TaC powder can be promoted to shrink tightly, recrystallize and grow to produce certain pores, and the excess carbon powder will volatilize and sublimate at high temperature and promote the generation of pores, thereby achieving the effect of improving the mechanical properties of the ceramic and generating pores, thereby improving various properties of the ceramic at high temperature.
[0066] 2. In the case of porous TaC ultrahigh temperature ceramics, the average particle size of the powder of the mixture is limited to
[0067] 1μm-5μm, which can improve the cold pressing rate and promote the stability of ceramic sintering process. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 This is the scanning electron microscope (SEM) image of the ceramic prepared in Example 1 (the scale of the left image is 5 μm, and the scale of the right image is 1 μm).
[0069] Figure 2 This is a scanning electron microscope (SEM) image of the ceramic prepared in Comparative Example 1 (the scale of the left image is 20 μm, and the scale of the right image is 5 μm). Figure 3 This is the scanning electron microscope (SEM) image of the ceramic prepared in Comparative Example 2 (the scale of the left image is 100 μm, and the scale of the right image is 30 μm).
[0070] Figure 4 This is the scanning electron microscope (SEM) image of the ceramic prepared in Example 2.
[0071] Figure 5 This is the scanning electron microscope (SEM) image of the ceramic prepared in Example 3.
[0072] Figure 6This is the scanning electron microscope (SEM) image of the ceramic prepared in Example 4.
[0073] Figure 7 This is a scanning electron microscope (SEM) image of the ceramic prepared in Comparative Example 3.
[0074] Figure 8 This is a scanning electron microscope (SEM) image of the ceramic prepared in Comparative Example 4.
[0075] Fig. 9 This is a scanning electron microscope (SEM) image of the ceramic prepared in Comparative Example 5.
[0076] Fig.10 This is the scanning electron microscope (SEM) image of the ceramic prepared in Comparative Example 6.
[0077] Fig.11 This is a scanning electron microscope (SEM) image of the ceramic prepared in Comparative Example 7.
[0078] Fig.12 This is a scanning electron microscope (SEM) image of the ceramic prepared in Comparative Example 8.
[0079] Fig.13 This is a scanning electron microscope (SEM) image of the ceramic prepared in Comparative Example 9.
[0080] Fig.14 This is a scanning electron microscope (SEM) image of the ceramic prepared in Comparative Example 10. DETAILED DESCRIPTION
[0081] The present invention provides a porous TaC ultra-high temperature ceramic and a preparation method thereof, wherein pores with large specific surface area and adjustable porosity are introduced into the ultra-high temperature ceramic to prepare the porous ultra-high temperature ceramic. The material not only maintains good fracture strength, but also significantly enhances gas adsorption and filtration capabilities. Therefore, it can be used as a new type of high-temperature filter material. In addition, its unique pore structure is also suitable for use in crystal growth guide elements to optimize the crystal growth process. The preparation method of the present invention is expected to improve the mechanical properties, thermal shock resistance and corrosion resistance of the material in a high temperature environment by regulating the porosity and ceramic microstructure, but the specific improvement effect of the relevant properties needs to be verified through further experimental tests.
[0082] Example 1
[0083] A porous TaC ultra-high temperature ceramic is prepared by using pore-forming agent and TaC powder as raw materials; the pore-forming agent is a metal element, carbon powder and metal oxide.
[0084] The weight ratio of the TaC powder, the metal element, the carbon powder and the metal oxide is 15:1:1:1.
[0085] The TaC powder (purity 99.95wt%, average particle size 3 microns, produced by Shanghai MacLean Biochemical Technology Co., Ltd., T819531-250g).
[0086] The metal oxide is iron oxide (purity of 99.95 wt %, average particle size of 1 micron, produced by Shanghai MacLean Biochemical Technology Co., Ltd., I857137-100g).
[0087] The carbon powder (purity 99.5wt%, average particle size 30nm, produced by Shanghai MacLean Biochemical Technology Co., Ltd., C805116-500g).
[0088] The metal element is cobalt (cobalt powder, purity 99.5wt%, average particle size 1 micron, produced by Shanghai MacLean Biochemical Technology Co., Ltd., C997307-100g).
[0089] A method for preparing porous TaC ultrahigh temperature ceramics comprises the following steps:
[0090] S1, putting the TaC powder and the pore-forming agent into a tungsten carbide ball mill, the ball mill medium is tungsten carbide, and grinding at a speed of 500 r / min for 24 hours to complete the mixing and homogenization of the powders.
[0091] S2, weighing 2.65 g of the mixed powder, and pressing at 25°C and 6 MPa for 2 min to form an embryo with a thickness of 3.15 mm and a diameter of 10 mm;
[0092] S3, place the embryo body into a graphite crucible with a supporting angle, in a slightly positive pressure (103 kPa) argon atmosphere, first increase the temperature to 1500°C at 3°C / min, then increase the temperature to 2000°C at 2°C / min, and then increase the temperature to 2600°C at 1°C / min, and continue to keep warm for 0.5h. After the insulation is completed, first cool down to 2000°C at 1°C / min, then cool down to 1500°C at 2°C / min, and then cool down to 25°C at 3°C / min.
[0093] Example 2
[0094] The specific implementation is the same as that of Example 1; the difference is that the metal element in the pore-forming agent of Example 2 is titanium, and the weight ratio of the TaC powder to the metal element is 30:1.
[0095] Example 3
[0096] The specific implementation is the same as that of Example 2; the difference is that the weight ratio of the TaC powder to the metal element is 10:1.
[0097] Example 4
[0098] The specific implementation is the same as that of Example 2; the difference is that the weight ratio of the TaC powder to the metal element is 1:1.
[0099] Comparative Example 1
[0100] The specific implementation is the same as Example 1; the difference is that the weight ratio of TaC powder, metal element, carbon powder and metal oxide in Comparative Example 1 is 30:1:1:1.
[0101] Comparative Example 2
[0102] The specific implementation is the same as Example 1; the difference is that the pore-forming agent in Comparative Example 2 is a metal element (cobalt), and the weight ratio of the TaC powder to the metal element is 30:1.
[0103] Comparative Example 3
[0104] The specific implementation is the same as in Example 1; the difference is that the metal oxide in Comparative Example 3 is Al 2 O 3 .
[0105] Comparative Example 4
[0106] The specific implementation is the same as in Example 1; the difference is that the metal oxide in Comparative Example 4 is TiO 2 .
[0107] Comparative Example 5
[0108] The specific implementation is the same as in Example 1; except that the metal oxide in Comparative Example 5 is SiO 2 .
[0109] Comparative Example 6
[0110] The specific implementation is the same as in Example 1; the difference is that the metal oxide in Comparative Example 6 is ZrO 2 .
[0111] Comparative Example 7
[0112] The specific implementation is the same as in Example 1; the difference is that the TaC powder in Comparative Example 7 is replaced by Ta 2 O 5 , 2 O 5 The weight ratio of powder, carbon powder, metal element and metal oxide is adjusted to 33:6:1:1.
[0113] Comparative Example 8
[0114] The specific implementation is the same as Example 1; the difference is that the TaC powder in Comparative Example 8 is replaced by Ta powder, and the weight ratio of Ta powder, carbon powder, metal element and metal oxide is adjusted to 15:15:1:1.
[0115] Comparative Example 9
[0116] The specific implementation is the same as that of Example 2; the difference is that the metal element in the pore-forming agent in Comparative Example 9 is nickel, and the weight ratio of the TaC powder to the metal element is 30:1.
[0117] Comparative Example 10
[0118] The specific implementation is the same as that of Example 2; except that the metal element in the pore-forming agent in Comparative Example 10 is manganese, and the weight ratio of the TaC powder to the metal element is 30:1.
[0119] Performance testing methods and data
[0120] The porosity and compressive fracture strength of the ceramics prepared in Examples 1-4 and Comparative Examples 1-2 were tested, wherein the porosity test was based on the method for determining the apparent porosity of carbon materials GB / T 24529-2009, and the porosity was calculated according to the formula: P = (m 2 -m 1 ) / (m 2 -m 3 )*100%(P is the apparent porosity (%), m 1 is the mass of the dry sample, m 2 is the mass of the saturated sample in air, m 3 is the mass of the saturated sample in water, and the mass unit is g), and the testing equipment is a Mettler Toledo XSR104 density balance; the compression fracture strength test refers to the metal compression test (GB / T7314-2005), the sample diameter (d) is 8.66mm, the original gauge length (L0) is 3.88mm, and the testing equipment is a LE5255 high and low temperature static testing machine. As shown in Table 1, the porosity of the porous TaC ceramics prepared in the five cases shows a positive correlation with the compression fracture strength, and the highest porosity of 39.61% and the better compression fracture strength of 542.5Mpa are achieved in Example 4.
[0121] The ceramics prepared in Example 1 and Comparative Examples 1-2 were characterized by scanning electron microscopy (SEM). Figure 1 As shown, the porous TaC ceramic formed in Example 1 has uniform pore distribution, good crystal shape, and exhibits excellent structural characteristics; Figure 2 As shown, the porosity of the ceramic in Example 2 is significantly reduced compared with that in Example 1, indicating that the pore structure is more compact; Figure 3 As shown, the ceramic pores in Example 3 are basically only present at the grain boundaries, TaC crystals form larger sizes, and are the most dense overall. These three cases show that the porosity and density of ceramic materials can be effectively regulated through different preparation processes, thereby achieving precise adjustment of the material application performance to meet the needs of different scenarios.
[0122] like Figure 4 As shown, the pore-forming agent is a metal element (titanium), and when the weight ratio of the TaC powder to the metal element is 30:1, the TaC ceramic has been well crystallized, and there are uneven and fewer pores; Figure 5 As shown, when the ratio is 10:1, the pores are uniform and the pore size is 1-3 microns; Figure 6 As shown, when the ratio is 1:1, the pores are 30-100 μm, and the sample also has only TaC component converted to (TaTi)C 2 These porous ceramics with different pore sizes are only related to the type and content of specific metal elements, and different pore sizes are used for different filtering and diversion conditions. Ceramics with smaller pore sizes are suitable for precision filtration, while those with larger pore sizes can be used for diversion or other special industrial environments.
[0123] like Figure 8 As shown, when taking TiO 2 When the ceramic is loose as a whole, it is fragile and easy to fall off, indicating that the material strength is insufficient; Fig. 9 As shown, the metal oxide is SiO 2 When the ceramic was severely delaminated and damaged, a large number of cracks were generated, and the appearance turned gray, indicating that the material structure was unstable, so no further analysis was performed; Figure 7 As shown, take Al 2 O 3 When , TaC ceramics are well crystallized, but the pores are uneven in size and small in number, and cracks appear on the ceramic surface, indicating that its structural integrity has decreased; Fig.10 As shown, when ZrO 2 When the TaC ceramics are oxidized, there is no obvious deformation on the outside, but the pores are mixed and disorderly distributed, lacking structural uniformity. It can be seen that different metal oxides have a significant effect on the structure and properties of TaC ceramics. 2 and TiO 2 The results after addition showed that it was not suitable for use as a pore-forming agent in the preparation of TaC ceramics, while Al 2 O 3 and ZrO 2 Although there are certain improvements in crystallization and deformation, there are still problems of pores and cracks, and the preparation process needs to be further optimized.
[0124] like Fig.11 As shown, select Ta 2 O 5 When the process is carried out, TaC ceramics undergo obvious deformation and shrinkage, and the pore distribution is not uniform, indicating that the pore structure under this process condition has not yet reached the ideal state; Fig.12 As shown, when Ta powder is used, TaC ceramics have a non-porous structure and are brittle, and the toughness of the material is poor, which cannot meet the requirements for strength and porosity.
[0125] like Fig.13 As shown in Figure 2, the prepared porous ceramics have small grain size, many pores, and obvious cracks, such as Fig.14 As shown, the prepared ceramics are only agglomerates of powders, the grain size is at the nanometer level, and there is no porous structure, that is, manganese and nickel are difficult to be used as preferred pore-forming agents.
[0126] Table 1
[0127]
Claims
1. A porous TaC ultrahigh temperature ceramic, characterized in that: The porous TaC ultra-high temperature ceramic is sintered by preparing raw materials, the preparing raw materials include a pore former and TaC powder, the pore former includes a first pore former and a second pore former; the first pore former includes a metal element and carbon powder, and the second pore former includes a metal oxide that can react with TaC, wherein the porous TaC ultra-high temperature ceramic has a porosity of 5%-40%, a compression fracture strength of ≥500Mpa, a melting point of the metal element is T1, a melting point of the second pore former is T2, and 1495°C≤T1≤T2.
2. The porous TaC ultrahigh temperature ceramic according to claim 1, characterized in that: In the preparation raw material, the weight ratio of the pore former to the TaC powder is 1:(1-10).
3. The porous TaC ultrahigh temperature ceramic according to claim 2, characterized in that: In the preparation raw material, the weight ratio of the pore former to TaC powder is 1:(2-8).
4. The porous TaC ultrahigh temperature ceramic according to claim 1, characterized in that: In the pore-forming agent, the weight ratio of the metal element, the carbon powder and the metal oxide is 1:(0.2-5):(0.2-5).
5. The porous TaC ultrahigh temperature ceramic according to claim 1, characterized in that: The melting point T1 of the metal element is 1495°C-3000°C.
6. The porous TaC ultrahigh temperature ceramic according to claim 1, characterized in that: The metal element includes at least one of titanium, iron, cobalt, nickel, molybdenum, chromium and zirconium.
7. The porous TaC ultrahigh temperature ceramic according to claim 1, characterized in that: The metal oxide includes at least one of iron oxide, aluminum oxide, copper oxide, titanium dioxide and iridium dioxide.
8. A method for preparing the porous TaC ultrahigh temperature ceramic according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mixing the TaC powder and the pore-forming agent uniformly to form a mixture; cold pressing the mixture to form an embryo body; The embryo body is sintered in an inert gas atmosphere; wherein the average particle size of the powder of the mixture is 1 μm-5 μm.
9. The method for preparing the porous TaC ultrahigh temperature ceramic according to claim 8, characterized in that: The average particle size of the powder of the mixture is 1 μm-4 μm.
10. The method for preparing the porous TaC ultrahigh temperature ceramic according to claim 8, characterized in that: The sintering process steps include: first heating to 1300-1500°C at 3°C / min-5°C / min, then heating to 1500-2000°C at 1°C / min-3°C / min, then heating to 2000-2600°C at 0.3°C / min-2°C / min, and keeping warm for 0.1h-3h.
Citation Information
Cited By
High-strength stepped pore size distribution porous ultra-high-temperature carbide ceramic and preparation method thereof
CN120441340A
A porous ultra-high temperature carbide ceramic with high strength and stepped pore size distribution and its preparation method
CN120441340B
Porous TaC component as well as preparation method and application thereof
CN122482815A
Porous TaC component as well as preparation method and application thereof
CN122608416A